Damage and Cracking Prediction of AISI 410 Martensitic Stainless Steel at Elevated Temperatures. Issue 9 (10th April 2021) - Zhang, Yu; Guo, Biao; Li, Qiang; Li, Xiao; Jian, Jie; Jin, Yingrong; Ao, Jinqing
Abstract : Combining Gleeble hot compression and tensile tests with finite‐element (FE) simulations, this study delivers a robust assessment of the elevated temperature damage and cracking of AISI 410 martensitic stainless steel. The effects of hot deformation parameters on the macroscopic flow and deformation behaviors as well as microscopic damage and fracture characteristics are discussed, determining the critical damage values with the aid of FE calculations. Furthermore, a novel critical damage value model is proposed using the Zener–Hollomon parameter to establish the normalized Oyane fracture criterion coupling hot deformation parameters. The results reveal that the flow stress and tensile load both increase, as the strain rate increases and the temperature decreases and vice versa. The occurrence of localized necking and internal damage cracking causes the tensile load to decline drastically. The hot deformation parameters manipulate not only the plat and dimple fractures, each caused by intergranular and transgranular fractures, but also the internal damage cracking before the final fracture. The established criterion predicts outcomes in good agreement with experimental results. This work provides essential information and a model for the cracking prediction of AISI 410 steel at elevated temperatures, helping to derive a rational hot forming design to prevent cracking. Abstract : Hot tensile damage and cracking of AISI 410 martensitic stainless steel are assessed. Finite‐element (FE)‐aided tests are used to determine the critical damage values of the steel. A novel critical damage value model is proposed using the Zener–Hollomon parameter. A normalized Oyane fracture criterion with high accuracy is established and verified.